The role of RNA-binding proteins in orchestrating germline development in Caenorhabditis elegans - Albarqi, Mennatallah M. Y.; Ryder, Sean P. (Frontiers in Cell and Developmental Biology, 2023)
RNA passed from parents to progeny controls several aspects of early development. The germline of the free-living nematode Caenorhabditis elegans contains many families of evolutionary conserved RNA-binding proteins (RBPs) that target the untranslated regions of mRNA transcripts to regulate their translation and stability. In this review, we summarize what is known about the binding specificity of C. elegans germline RNA-binding proteins and the mechanisms of mRNA regulation that contribute to their function. We examine the emerging role of miRNAs in translational regulation of germline and embryo development. We also provide an overview of current technology that can be used to address the gaps in our understanding of RBP regulation of mRNAs. Finally, we present a hypothetical model wherein multiple 3´UTR-mediated regulatory processes contribute to pattern formation in the germline to ensure the proper and timely localization of germline proteins and thus a functional reproductive system.